Transition-Metal-Catalyzed Cleavage of C–N Single Bonds - Ouyang, Kunbing; Hao, Wei; Zhang, Wen-Xiong; Xi, Zhenfeng (Chemical reviews, 2015)
The transition-metal-catalyzed cleavage of the carbon-nitrogen bond is examined. This is a chemical bond that exists in biomacromolecules and organic molecules.